Assessment of the influence of foot orthoses in the hip loading conditions during walking: a single case study - Pustoc'h, A.; Bonnefoy, A.; Labesse-Jied, F.; Lavigne, A.; Cheze, L. (Computer Methods in Biomechanics and Biomedical Engineering, 2011)
Despite their large clinical application, the understanding of the effects of foot orthoses on the lower limb kinematics and kinetics is limited. In this context, we propose an advanced musculoskeletal model to assess the influence of foot orthoses in the loading conditions within an osteoarthritic hip joint during gait. Experimental data are collected for a single pathological subject presenting a coxarthrosis (with and without orthoses), and a healthy subject during walking. An inverse dynamic approach coupled with an optimisation method evaluates the forces developed by 14 muscles and the hip contact reaction force. Contact reaction and muscular force magnitudes are closed whether the patient is walking with or without foot orthoses. Nevertheless, contact reaction amplitudes and orientations show differences in relation to those calculated for the healthy subject. The results obtained allow us to formulate some assumptions concerning the causes of coxarthrosis evolution and treatment.